Expanding Underrepresented in Medicine to Include Lesbian, Gay, Bisexual, Transgender, and Queer Individuals. (3rd May 2022) - Kelly, Tim; Rodriguez, Sarah B.
Abstract : In 2003, the Association of American Medical Colleges (AAMC) stopped using the term "underrepresented minority" and instead adopted "underrepresented in medicine." This was not the first time the AAMC revised this definition. In this article, the authors call on the AAMC to revise and expand this definition to include another group that is underrepresented in medicine: lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals. It is difficult to know whether LGBTQ populations are underrepresented in medicine; however, the data that do exist suggest a significant lack of LGBTQ representation in medicine. It is unclear if this underrepresentation is due to a true numerical lack of LGBTQ physicians, to LGBTQ physicians not publicly self-identifying due to anti-LGBTQ sentiments and reactions, or to both. The authors urge the AAMC to take 3 actions: to anonymously and sensitively poll physicians nationwide to obtain a better estimate of the current number of LGBTQ physicians, to formulate improved standards for an LGBTQ health curriculum for all medical trainees to consistently produce LGBTQ-competent physicians, and to once again expand its definition of underrepresented in medicine to include LGBTQ populations. Such a change to this definition would likely lead to concerted efforts to increase the number of LGBTQ physicians, which could then lead to increased visibility, inclusivity, and mentorship programs where LGBTQ trainees could thrive. With these 3 actions, the authors believe that the AAMC has the opportunity to forge a path forward that is not only beneficial to LGBTQ trainees but also to LGBTQ patients who currently face a myriad of health disparities due to the lack of LGBTQ-identifying and LGBTQ-competent physicians.